The Authentication of Information in Egovernment in Administrative Law in Poland - Błażewski, Maciej (University of Wroclaw. Faculty of Law, Administration & Economics, 2017)
The process of authentication of information is connected with the transfer of information in e-government. Provisions of e-government regulate the rights and obligations of participants in this process. These provisions are expressed in national and in European law. These participants are providers of authentication of information. The process of authentication of information is only partially unified, because of implementation of the provisions of European law. Means of authentication of information in e-government are necessary to determine the identity of the sender of information. There are types of means of authentication of information. They are ranked in order from largest to smallest degree of security of information. These types include: the qualified means of authentication of information, the public website and the private website. The type of means of authentication of information is coherent with the type of transferred information and the type of recipient of the information.
Keywords: authentication of information; e-government; administrative law; Poland